Factors Impacting σ- and π-Hole Regions as Revealed by the Electrostatic Potential and Its Source Function Reconstruction: The Case of 4,4′-Bipyridine Derivatives - Carlo Gatti; Alessandro Dessì; Roberto Dallocchio; Victor Mamane; Sergio Cossu; Robin Weiss; Patrick Pale; Emmanuel Aubert; Paola Peluso (Molecules, 2020)
Positive electrostatic potential (V) values are often associated with σ- and π-holes, regions of lower electron density which can interact with electron-rich sites to form noncovalent interactions. Factors impacting σ- and π-holes may thus be monitored in terms of the shape and values of the resulting V. Further precious insights into such factors are obtained through a rigorous decomposition of the V values in atomic or atomic group contributions, a task here achieved by extending the Bader–Gatti source function (SF) for the electron density to V. In this article, this general methodology is applied to a series of 4,4′-bipyridine derivatives containing atoms from Groups VI (S, Se) and VII (Cl, Br), and the pentafluorophenyl group acting as a π-hole. As these molecules are characterized by a certain degree of conformational freedom due to the possibility of rotation around the two C–Ch bonds, from two to four conformational motifs could be identified for each structure through conformational search. On this basis, the impact of chemical and conformational features on σ- and π-hole regions could be systematically evaluated by computing the V values on electron density isosurfaces (VS) and by comparing and dissecting in atomic/atomic group contributions the VS maxima (VS,max) values calculated for different molecular patterns. The results of this study confirm that both chemical and conformational features may seriously impact σ- and π-hole regions and provide a clear analysis and a rationale of why and how this influence is realized. Hence, the proposed methodology might offer precious clues for designing changes in the σ- and π-hole regions, aimed at affecting their potential involvement in noncovalent interactions in a desired way.